Pharmaco-economic inequalities in access to antifibrotic treatment for interstitial lung disease in the Asia-pacific region - Felix Chua; Larry Ellee Nyanti; Shirin Hui Tan; Syazatul Syakirin Sirol Aflah; Sze Shyang Kho; Gin Tsen Chai; Amornpun Wangkarnjana; Su-Ying Low; Sita Andarini; Lutz Beckert; Celeste May Campomanes; Florence KP Chan; et al. (National Library of Medicine, 2025)
Antifibrotic drugs, available for the best part of the last decade in many parts of the world, have improved outcomes in patients with idiopathic pulmonary fibrosis and progressive pulmonary fibrosis. However, it is unclear whether patients suffering from these devastating conditions have timely and adequate access to antifibrotic therapy in the Asia-Pacific region (APAC). In this mixed-methods narrative review of 12 APAC countries, integration of questionnaire-based insights of 31 regional clinical experts in interstitial lung disease (ILD) with publicly available pharmaco-economic information has been used to understand how country-specific challenges impact on antifibrotic accessibility. Overall, a broad range of approaches are utilized to provide antifibrotic treatment including centrally or state-determined drug budgets, pharmaceutical industry-subsidized initiatives, charitable support and self-paying (out-of-pocket) options. Impediments to antifibrotic access commonly arise from prohibitive drug pricing in relation to income, absence of universal coverage for pharmaceutical costs, lack of formal pharmaco-economic analysis or restrictions on the use of generic preparations. Unequal access to antifibrotic drugs is a vital unmet therapeutic need in the APAC region, one that is likely to be exacerbated by a rising fibrotic ILD burden.